New Trends in the Apparel Industry: Exploring New Access-Based Consumption Models in the Mexican Market - Cacho-Elizondo, Silvia (Journal of Marketing Development and Competitiveness, 2023)
Building on the access-based consumption and sharing economy literature, this research explores new trends of apparel consumption among Mexican women. The methodology used is a qualitative approach based on 12 in-depth interviews. The field research took place in the three main cities of Mexico: Mexico City, Monterrey, and Guadalajara. The analysis found different ways to access apparel: a) lending; b) renting from a physical store; c) renting from an online website; d) shared purchase; e) online purchase; and f) purchase from a physical store. Therefore, participants mentioned more alternatives for accessbased consumption than for traditional purchase models. The possession of things (ownership model), especially status possessions such as clothes and accessories, is far from disappearing. However, it is important to better understand the scope and impact of the access-based consumption model in developing countries.